The Routledge handbook of the history of translation studies - Lange, Anne; Monticelli, Daniele, 1970-; Rundle, Christopher, 1963- (Routledge handbooks in translation and interpreting studies., 2024)
"The Routledge Handbook of the History of Translation Studies is an exploration of the history of translation and interpreting studies (TIS) as a field of intellectual enquiry. The volume covers the evolution of thinking on translation, from the earliest discourses in Assyria, Egypt, Israel, China, India, and Greece, up to the early 20th century when TIS emerged as an identifiable academic field. The volume also traces the institutionalization of TIS and its key concepts from their beginnings in the 1930s in Ukraine up to their contemporary interdisciplinary manifestations. Written by leading international scholars, many of whom played a direct role in the events they describe, the chapters in this volume provide a comprehensive and in-depth account of the birth and consolidation of translation and interpreting studies as a thriving interdiscipline. With a focus on providing readers with the methodological and theoretical tools they need to conduct research, as well as background in the historiography of TIS, this handbook is an indispensable resource for all students and researchers of translation and interpreting studies"--